Answer:
-6
Step-by-step explanation:
3n = n² - 54
n² - 3n - 54 = 0
n² - 9n + 6n - 54 = 0
n(n - 9) + 6(n - 9) = 0
(n - 9)(n + 6) = 0
n = 9 , -6
For the first equation, the answer is C) completing the square.
For the second equation, the answer is B) zero product property.
For the first equation, we can easily complete the square by finding half of b and squaring it; then we can take the square root of both sides and solve the equation.
For the second equation, since it is already factored, we use the zero product property to solve it.
4 (k-6)-(3k+2)=-5
4k-24-3k-2=-5
k-26=-5
k=21
Answer:
b = -18
Step-by-step explanation:
(3 + 4i) (-3-2i)
When we foil:
-9 + -6i + -12i + -8i^2
-8i^2 = +8
Combine like terms:
-1 + -18i
Answer:
56
Step-by-step explanation:
x+x+8=104
2x=96
x=48
48+8=56